Topical Therapeutic Options in Corneal Neuropathic Pain - Nortey, Jeremy; Smith, David; Seitzman, Gerami D.; Gonzales, John A. (Frontiers in Pharmacology, 2022)
Purpose of Review: Corneal neuropathic pain can be difficult to treat, particularly due to its lack of response to standard dry eye therapies. We describe a variety of topical therapeutic options that are available to treat corneal neuropathic pain with a significant or primary peripheral component. We also describe possible mechanisms of action for such topical therapies. Recent Findings: Topical corticosteroids and blood-derived tear preparations can be helpful. Newer therapies, including topical lacosamide and low-dose naltrexone are emerging therapeutic options that may also be considered. Summary: Corneal neuropathic pain with a significant peripheral component may be managed with a variety of topical therapeutic options.